Si-Miao-Yong-An Decoction for Diabetic Retinopathy: A Combined Network Pharmacological and In Vivo Approach - Du, Ao; Xie, Yumin; Ouyang, Hao; Lu, Bin; Jia, Wangya; Xu, Hong; Ji, Lili (Frontiers in Pharmacology, 2021)
Si-Miao-Yong-An decoction (SMYAD), a traditional Chinese medicine formula, is mainly used to clear away heat and detoxify, and to promote blood circulation and relieve pain. Diabetic retinopathy (DR) is the most common type of microvascular complication caused by diabetes. This study is designed to examine the protective effect of SMYAD against DR, and further to reveal the engaged mechanism via integrating network pharmacology and in vivo experimental evidences. Streptozotocin (STZ) was intraperitoneally injected to mice to induce diabetes. The dysfunction of blood-retina-barrier (BRB) was observed by conducting Evan’s blue leakage assay, detecting tight junction (TJ) protein expression and counting the number of acellular capillaries in retinas. Our results showed that SMYAD attenuated BRB breakdown in vivo. Network pharmacology demonstrated that regulating inflammation and immune responses, and angiogenesis may be associated with the alleviation on DR provided by SMYAD. Tumor necrosis factor (TNF) and hypoxia inducible factor 1 (HIF1) signal pathways were critically involved in the SMYAD-supplied amelioration on DR. Next experimental results showed that SMYAD decreased microglia activation in retinas and reduced the enhanced adhesion of leukocytes into retinal vessels. SMYAD reduced the elevated serum TNF content and retinal TNF expression. SMYAD reduced nuclear factor B (NFB) activation and its downstream pro-inflammatory molecules expression in retinas. SMYAD also decreased HIF1 activation and its downstream vascular endothelial growth factor (VEGF) expression in retinas. These results indicated that SMYAD attenuated DR development through suppressing retinal inflammation and angiogenesis via abrogating NFB-TNF and HIF1-VEGF signal pathways.